Late Pleistocene ecological, environmental and climatic reconstruction based on megafauna stable isotopes from northwestern Chilean Patagonia. (15th August 2017) - González-Guarda, Erwin; Domingo, Laura; Tornero, Carlos; Pino, Mario; Hernández Fernández, Manuel; Sevilla, Paloma; Villavicencio, Natalia; Agustí, Jordi
Abstract: Stable isotope analyses have been performed on the bioapatite (δ 13 C; δ 18 O) and collagen (δ 13 C; δ 15 N) of four late Pleistocene South American megafaunal taxa ( Notiomastodon platensis, Equus andium, cf. Hemiauchenia paradoxa and Xenarthra indet.) to evaluate paleoclimatic and paleoenvironmental conditions as well as paleoecological features of this time period. The analyzed megafauna was found at several locations in the northwestern Chilean Patagonia (38°–42°S, 74°–71°W). The bioapatite δ 13 C values indicated the presence of C3 vegetation ranging from forestal to woodland areas. The collagen δ 15 N values pointed to temperate and humid ecosystems, and to the consumption of shrubs, trees, grasses and sedges. Mean annual temperatures estimated from bioapatite δ 18 OPO4 values show a similarity to modern temperatures and suggested that the megafauna under study may have lived during warm stages (interstadials) of the late Pleistocene. When comparing our results with those obtained from other South American regions, we find that the diet of this particular Chilean megafauna appears to have been more influenced by resource availability than by the potential dietary range of the taxa. Highlights: Bioapatite δ 13 C values indicate C3 vegetation from forestal to woodland areas. Collagen δ 15 N values point to temperate and humid ecosystems. Estimated mean annual temperatures from δ 18 OPO4 values similar to the modern ones. Chilean megafauna diet dominated by the availability of resources.